Pharmacodynamics of colistin against Acinetobacter baumannii - Mohd Rasidin, Rashizal Sazli (2017)
Nosocomial infection caused by Acinetobacter baumannii is endemic in hospital settings especially among immunocompromised patients. Treatment strategy is limited due to rapid emergence of extensively drug resistance and lack of novel agent in the antibiotic development pipeline. Colistin has been the last line therapy with good in vitro activity. However, updates in the pharmacological aspects are required to support dosing optimisation. The current study descriptively explained high proportion (89%) of extensively drug resistance among 72 multidrug resistance strains of A. baumannii collected from Hospital Serdang. The clinical strains were mainly isolated from elderly patients (median age 61 [IQR 25]) admitted to medical ward (35%) while common isolation site was respiratory sample (60%). Antibiogram profile showed 100% in vitro susceptibility of the strains to colistin with 54% of isolates exhibit MIC 1.0 μg/mL. The in vitro static time-kill kinetic and post-antibiotic effect experiments were conducted against two clinical isolates (colistin MIC 1.0 μg/mL and 0.75 μg/mL) as well as one reference isolate ATCC 19606 (colistin MIC 1.0 μg/mL). The development of colistin resistance was also examined after colistin exposure in time-kill study. The post-antibiotic effect was determined at colistin concentration based on the achievable plasma level after parenteral administration. Concentration-dependent killing activity was observed in time-kill experiment against all studied isolates. However, delayed bactericidal activity indicates tolerance or persistence of the strains against colistin. Development of colistin resistance after colistin exposure was not detected except for the known colistin heteroresistance ATCC 19606 strain. Meanwhile, the post-antibiotic effect was significant in a concentration-dependent manner for all studied isolates. Dosing suggestion based on observations from this study include administration of a supplemental dose 3 MIU at 12 hours after loading dose, administration of maintenance dose 9 MIU in two divided doses and the application of extended interval in dosing adjustment for patients with renal impairment. However, information of the current study is applicable for non-colistin-heteroresistance A. baumannii with colistin MIC ≤ 1 μg/mL. As for heteroresistance and strain with colistin MIC > 1.0 μg/mL, combination therapy would be the more appropriate treatment strategy.